Wakaf Produktif Sebagai Strategi Pemberdayaan Ekonomi Masyarakat Menuju Pembangunan Berkelanjutan di Era 4.0 - Siti Sundari (LPPM IAIT, 2023)
The potential of waqf has become one of the greatest potentials that can produce something beneficial for economic growth in Indonesia if it can be optimally utilized supported by competent human resources in the management process. Productive waqf empowerment is an effort to develop and manage waqf assets through various empowerment programs so that the benefits are sustainable and the waqf can be distributed evenly. Waqf here can be divided into waqf of immovable objects such as land and waqf of movable objects such as money. On the other hand, with the development of technology, many new innovations have emerged in the world of finance, namely financial technology (fintech). The purpose of this study is to provide a strategic overview of the empowerment of productive waqf in the economic welfare of the community. The method used in this study is a qualitative approach to literature study with descriptive methods. The results of this study indicate that a strategic effort in empowering productive waqf to realize the economic welfare of the community is by optimizing the role of the nazir which includes developing human resources, increasing nazir welfare and improving regulations related to waqf and optimizing the empowerment of productive waqf which includes optimizing aspects of waqf management and distribution , innovation in the concept of empowerment programs, increasing synergy with several related agencies, developing the potential of e-waqf, and involving waqf as one of the government's fiscal